[RETRACTED] Traditional ecological knowledge in conserving marine resources in Terengganu, Malaysia - WAN IZATUL ASMA WAN TALAAT; SYUHADA MD JUHARI; NORIZAN ESA; SALASIAH CHE LAH; BADARUDDIN MOHAMAD (Nusantara Bioscience, 2018)
Talaat WIAW, Md Juhari S, Esa N, Che Lah S, Mohamad M. 2018. Traditional ecological knowledge in conserving marine resources in Terengganu, Malaysia. Nusantara Bioscience 10: 6-11. Conserving marine resources to ensure its sustainable supply requires concerted effort by all the stakeholders including the local fishermen. The zoning of MPAs by the government is a formal method of conserving marine resources where some efforts of conservation on the specified areas are demonstrated. Currently, in the Terengganu waters, which sits in the southernmost part of the South China Sea, the only MPAs are the 13 islands/areas zoned as marine parks amounting to 568.69km2. Nonetheless, protecting or conserving marine resources cannot be limited to areas surrounding these marine parks alone. With 244km coastline and fishing is inherently a major economic activity in the state, more areas in the Terengganu waters should be designated as MPAs or alternatively gazetted as ecologically sensitive areas. In order to conserve marine resources to ensure its sustainable supply, a concerted effort must be carried out by all the stakeholders including the local communities, whose livelihood are directly impacted. As repositories of knowledge with regard to biodiversity, habitats and their seasonal fluctuations, the local communities must also be appreciated as resource users. The local fishermen’s TEK including familiarity with the use of sustainable fishing methods and practices are indeed pertinent for the sustainable supply of marine resources. This paper discusses the existing marine conservation efforts in Terengganu as well as explores the possibility of factoring in the local communities’ local knowledge through collaborative management to enhance these efforts.